Global Warming Potential* (GWP*): Understanding the implications for mitigating methane emissions in agriculture - Costa, Ciniro; Wironen, Michael; Racette, Kelly; Wollenberg, Eva Karoline (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
KEY MESSAGES: - GWP* (global warming potential) complements conventional climate metrics such as GWP100 because GWP* better describes the actual warming caused by methane (CH4) emissions. For example, using GWP100, a constant annual rate of CH4 emissions may be misinterpreted as having a 3-4 times higher impact on warming than observed. The use of GWP* can correct this misestimation. - GWP* was used here to evaluate the impact of agricultural CH4 emissions scenarios from 2020- 2040, finding that: - A sustained ~0.35% annual decline is sufficient to stop further increases in global temperatures due to agricultural CH4 emissions. This is analogous to the impact of net-zero CO2 emissions. - A ~5% annual decline could neutralize the additional warming caused by agricultural CH4 since the 1980s. - Faster reductions of CH4 emissions have an analogous impact to removing CO2 from the atmosphere. - However, a 1.5% annual increase in CH4 emissions would lead to climate impacts about 40% greater than indicated by GWP100. - The application of GWP* to CH4 emissions accounting suggests that avoiding further warming due to CH4 emissions in agriculture is more attainable than previously understood. CH4 reductions can have a rapid and highly substantial impact, which underscores the importance of making significant cuts in CH4 emissions immediately.